The Moderating Effect of Work-Life Balance on Job Satisfaction - Gounder, Simone; Govender, Patsy (Journal of Economics and Behavioral Studies, 2018)
In emerging cultures, job satisfaction and work-life balance are ongoing factors in gaining the ultimate competitive advantage for organizations. Work-life balance is a core ingredient for job satisfaction and for quality work performance, and employees need to have a sense of commitment to their jobs. The study attempts to determinethe extent to which work-life balance has a moderating effect onjob satisfaction in a call centre organization. The approach for the study was quantitative, and a self-developed questionnaire was the research instrument. The sample was107 employees and, both descriptive and inferential statistics were utilized. A probability random sampling technique was chosen. As evidenced in the study, room for improvement was required with both job satisfaction and work-life balance and; the validity and reliability for the study were high. The hypothesis for the study was partially accepted. In addition to a significant relationshipthat exists between the main constructs, work-life balance does have a moderating effect onjob satisfaction. The results and recommendations provide anecdotal evidence to call centre managers and policy makers to reach new levels of operations in order to meet their strategic intent and goal attainment.